2017
DOI: 10.1016/j.jid.2017.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine Use in Epidermal Necrolysis Is Associated with an Important Mortality Reduction: Evidence from Three Different Approaches

Abstract: Several immunomodulatory agents are used in the treatment of epidermal necrolysis, but evidence of their efficacy is limited. The Autonomous Community of Madrid has two reference burn units to which all patients with epidermal necrolysis are referred. One burn unit has mostly used cyclosporine (CsA), and the other has used non-CsA therapies (mainly high-dose intravenous immunoglobulin). The allocation of patients to one or the other burn unit was mainly based on proximity, resembling a random assignment. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(62 citation statements)
references
References 29 publications
(27 reference statements)
1
55
0
6
Order By: Relevance
“…Emerging data from Europe, including a meta-analysis and systematic review, report a mortality benefit from treatment with cyclosporine (Arévalo et al, 2000;Gonzalez-Herrada et al, 2017;Kirchhof et al, 2014;Lee et al, 2017;Reese et al, 2011;Valeyrie-Allanore et al, 2010;Zimmermann et al, 2017), whereas a more recent retrospective cohort study showed no benefit (Poizeau et al, 2018). Etanercept has also been reported beneficial in a small case series (Paradisi et al, 2014) and, recently, in a randomized trial (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data from Europe, including a meta-analysis and systematic review, report a mortality benefit from treatment with cyclosporine (Arévalo et al, 2000;Gonzalez-Herrada et al, 2017;Kirchhof et al, 2014;Lee et al, 2017;Reese et al, 2011;Valeyrie-Allanore et al, 2010;Zimmermann et al, 2017), whereas a more recent retrospective cohort study showed no benefit (Poizeau et al, 2018). Etanercept has also been reported beneficial in a small case series (Paradisi et al, 2014) and, recently, in a randomized trial (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The study also reported that there were no differences with respect to the development of renal failure requiring dialysis, bacteremia, and mechanical ventilation between those who received cyclosporine and those who did not. González-Herrada et al (2017) took advantage of a "natural experiment" by comparing two reference burn units in Madrid; one that utilizes cyclosporine in SJS/TEN treatment, whereas the other does not. Of 49 patients treated with cyclosporine, 11.8 were expected to die based on their SCORTEN score, however only five deaths were observed.…”
Section: Efficacymentioning
confidence: 99%
“…Its management includes offending agent withdrawal, supportive care, and use of systemic immunomodulators to halt disease progression. Cyclosporine is an immunosuppressant with favorable activity in SJS/TEN, producing near‐complete disease stabilization in 3 days and complete re‐epithelialisation by 12 days (González‐Herrada et al, ). Multiple studies demonstrate its efficacy, with two meta‐analyses reporting significant reduction in mortality in SJS/TEN (Ng, De Deyn, Venkatanarayanan, Ho, & Yeo, ; Zimmermann et al, ).…”
Section: Clinical Data and Details Of All Patients With Sjs/tenmentioning
confidence: 99%
“…Multiple studies demonstrate its efficacy, with two meta‐analyses reporting significant reduction in mortality in SJS/TEN (Ng, De Deyn, Venkatanarayanan, Ho, & Yeo, ; Zimmermann et al, ). Although most studies used oral cyclosporine, intravenous form has been utilized less frequently with success in few studies (González‐Herrada et al, ). Intravenous cyclosporine has added advantage of predictable bioavailability vis‐à‐vis oral cyclosporine (Morse, Holdsworth, Venuto, Gerbasi, & Walshe, ).…”
Section: Clinical Data and Details Of All Patients With Sjs/tenmentioning
confidence: 99%